Reversible, Selective, Ultrawide‐Range Variable Stiffness Control by Spatial Micro‐Water Molecule Manipulation (Adv. Sci. 20/2021). Issue 20 (21st October 2021) - Ha, Inho; Kim, Minwoo; Kim, Kyun Kyu; Hong, Sukjoon; Cho, Hyunmin; Kwon, Jinhyeong; Han, Seonggeun; Yoon, Yeosang; Won, Phillip; Ko, Seung Hwan
Abstract : Spatial Micro‐Water Manipulation An octopus with homogeneously soft structure can easily hide in rocks, where an athlete can throw javelin in precisely controlled manner thanks to the articular structure. Nature designed these distinctive structures by adjusting the amount of water inside. For taking both of their kinematics, the spatial micro‐water molecule manipulation maneuvers the amount of water in the hydrogel enabling the alteration between two structures. More details can be found in article number 2102536 by Seung Hwan Ko and co‐workers.